Realismo de 70 e neo-realismo português - Medeiros, Francisco Roberto Silveira de Pontes (2005)
This essay talks about the differences and similarities existent between the Realism of 1870 and the Neo-Realism in Portugal. Inside, the author searches for the theoretical sources of the Realism socialist that allowed to establish the distinction between the movements, as well as the contribution of each one in their historical context.